Sintesis One-Pot Komposit Reduced Graphene Oxide/Polipirrol (rGO/PPy) pada Substrat Stainless Steel Fleksibel sebagai Elektroda Superkapasitor - Nur Hayati; Nina Aprilini; Pratiwi Sanggusti; Rahmat Hidayat; Hidayat Hidayat; Maria Ulfa; Yahdi Bin Rus (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of portable, wearable, and flexible electronic devices has increased the demand for energy storage systems with high electrochemical performance, long cycle life, and good mechanical flexibility. In this study, a reduced graphene oxide/polypyrrole (rGO/PPy) composite electrode was successfully synthesized on a flexible stainlesssteel substrate using a one-pot electropolymerization method for flexible supercapacitor applications. The rGO electrode was first prepared by the doctor blade technique and subsequently modified through the electropolymerization of 5 mM pyrrole using Cyclic Voltammetry (CV). The electrochemical performance of the synthesized electrodes was evaluated through Cyclic Voltammetry, capacitance measurements, cycling stability tests for up to 1000 cycles, and bending tests to assess their mechanical flexibility. The results showed that the incorporation of PPy significantly enhanced the electrochemical response and increased the capacitance of the electrode compared with pristine rGO, indicating the additional contribution of pseudocapacitive charge storage. However, during the cycling stability test, the rGO electrode exhibited higher capacitance retention after 1000 cycles than the rGO/PPy electrode, suggesting that the PPy layer experienced gradual structural degradation during repeated charge–discharge processes. Despite this decrease in cycling stability, the bending test demonstrated that the rGO/PPy electrode maintained good structural integrity without visible cracking or delamination after mechanical deformation. These findings indicate that the one-pot electropolymerization method successfully produced an rGO/PPy composite electrode with improved electrochemical performance and good mechanical flexibility, demonstrating its potential as an electrode material for flexible supercapacitor applications.